2018
DOI: 10.7249/rr2413
|View full text |Cite
|
Sign up to set email alerts
|

Access to Medical Treatment for Injured Workers in California: Year 1 Annual Report

Abstract: This study was commissioned by the California Department of Industrial Relations (DIR) as mandated by California Labor Code Section 5307.2 (2009) to assess annually whether injured workers have adequate access to quality care under contract number 41336064. This independent assessment authorizes the administrative director to make appropriate adjustments in feeschedule amounts if the administrative director determines that there is inadequate access to care. The RAND Corporation has been commissioned to examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…other barriers that could prevent care. Specifically, a RAND report pointed out that stakeholders worried that changes to the fee schedule and medical treatment dispute processes might affect how some providers interact with WC patients and the WC system (Mulcahy et al, 2018).…”
Section: Medical Benefits ($)mentioning
confidence: 99%
See 1 more Smart Citation
“…other barriers that could prevent care. Specifically, a RAND report pointed out that stakeholders worried that changes to the fee schedule and medical treatment dispute processes might affect how some providers interact with WC patients and the WC system (Mulcahy et al, 2018).…”
Section: Medical Benefits ($)mentioning
confidence: 99%
“…A series of RAND reports evaluating access to care within the California WC system found that the timeliness of care in California's system compared favorably with those in other states and that most injured workers followed an appropriate pathway of care through treatment (Kapinos et al, 2018;Kapinos and Montemayor, 2019;Mulcahy et al, 2018;Mulcahy et al, 2020;Wynn et al, 2018). On the other hand, RAND also found that fewer providers were treating injured workers over time concurrent with an increase in claims, bill lines, and spending per provider, suggesting the possibility of increased provider concentration within the system.…”
Section: Medical Benefits ($)mentioning
confidence: 99%
“…Access to health care is defined by the Institute of Medicine as the timely use of personal health services to achieve the best possible health outcomes, and it is often measured in medical data by utilization of health services and health outcomes (Institute of Medicine, 1993). As discussed in the Year 1 report (Mulcahy et al, 2018), there are challenges to measuring access. In particular, we are unable to say much about access for individuals who do not receive care.…”
Section: Background and Key Objectivesmentioning
confidence: 99%
“…As noted in the Year 1 and Year 2 reports, there are two main approaches to attributing the dates of service in a given year (Mulcahy et al, 2018;Kapinos et al, 2018). First, we can define the service year, which includes all medical services-each of which corresponds to a bill line record-provided in a given calendar year.…”
Section: Analytic Approach Data and Study Samplementioning
confidence: 99%
See 1 more Smart Citation